'There are differences': Variants and Errors in the Texts of Beckett's Radio Plays. Issue 1 (April 2015) - Verhulst, Pim
Abstract : As opposed to Beckett's drama and, to a lesser degree, his television plays, the six scripts he wrote for radio are generally considered to be a textually stable category in his body of work. The only well-known exception is Cascando, whose American and British first editions were distinguished by more than fifty variants. When Everett Frost confronted the author with the Grove and Faber versions of the text in 1987, to re-record them for an American Festival of his radio plays, Beckett admitted 'there are differences' and advised the producer to follow the Faber example. Three years earlier, Beckett's English-language publishers had made the same choice for their joint publication of the Collected Shorter Plays (1984), when Grove discarded their texts of the radio plays for the Faber alternatives. But, not only were the American texts generally more reliable, they sometimes contained unique variants as well. Unproofed by the author, CSP added several new mistakes to the ones still surviving from the British first editions and their later reprints. This is problematic as CSP continued to serve as the model for Grove's Centenary Edition (2006) and Faber's All That Fall and Other Plays for Radio and Screen (2009). While its editor, Everett Frost, has 'made every effort silently to correct minor flaws appearing in earlier editions, no attempt has been made to impose a rigorous consistency upon such diverse materials'. Building on Frost's work, this article compares all English editions with each other, as well as the typescripts on which they were based, to provide an overview of variants and errors for each text. The purpose is to show that Cascando is not the only one marked by differences, and that a study of the existing drafts is necessary to fully understand the publishing history of the radio plays.